Иностранный язык (английский). Модуль 2 электронный курс - Овчинникова, Е. С. лингвист преподавательТомского политехнического университета 1986- (TPU Moodle, 2014)
В курсе "Иностранный язык (английский). Модуль 2" рассматриваются темы занятий, представленных в виде 2 модулей: Travelling, Healthy lifestyle (общей трудоемкостью 96 часов, из них СРС - 32часа). Изучается грамматический материал: Articles of landmarks, and sights; Past Simple, Present Perfect (active and passive); Adverbs: still, since, yet, already, etc.; Tenses: Present Perfect, Present Perfect Continuous; Causative forms; Modals expressing physical ability, advice, necessity, permission (can, should, may, must, have to); Imperative mood; Used to/would Modals expressing physical ability, advice, necessity, permission, prohibition (can, should, may, must, have to, mustn't, don't have to); Conditionals (0, 1, 2, 3); Word formation; Phrasal verbs.